Government balance-consistent economic growth rates and their implications: A study of the Euro area countries - Charalambos Pattichis (European Journal of Government and Economics (EJGE), 2020)
Using the model derived by Bajo-Rubio (2014), this paper estimates government budget balance-consistent growth rates for the euro area countries. A comparison of these estimates to their actual growth rates indicates that most of these countries are growing at rates that are very similar to their government balance-consistent growth rates. This finding implies that many euro area countries would not be experiencing excessive imbalances in their government budget over the long-run that could harm future economic growth. The analysis has also shown that for many euro area countries, the predictions of the model seem to be broadly consistent with their actual fiscal experience.
Keywords: E60; H60; H68; 330; balanced budget; budget deficits; economic growth